The Concept of Spiritual Humanism in Mulia Sadra’s Philosophi: an Analysis Study of the Existence of Modern Humans - Qoriah, Hidayatul; Khair, Nurul (Proceeding International Conference on Science and Engineering, 2020)
This paper is a review of Mulla Sadra’s thought library about the concept of spiritual humanism and its significance to human existence in the modern era. This paper aims to find out the meaning, principles, and nature of humanism in Mulla Sadra’s views through his main work entitled al-Asfar al-Arba’ah and some research on Mulla Sadra’s philosophical thinking. By using philosophical descriptive analysis, it can be concluded that the concept of Mulla Sadra’s humanism is studied and explored through the discourse of the soul. The implication, humans know and realize the existence of immaterial aspects in their existence is perfect. In addition to knowing that there is a material aspect to human existence, the humanism concept in Mulla Sadra’s view is to criticize the views of western philosophers, such as Jean Paul Sartre and Fredrich Nietzsche who view human existence based on material awareness. As a result, human existence is seen through the material side. The implication, human awareness is limited. In the modern era, the majority of people understand their existence as offered by western philosophers, so that the majority of people do not have awareness in realizing and knowing their existence, as they should. In addition, the views of western philosophers on material awareness in human existence cause freedom of will. Freedom of will in the western view causes dehumanism, because it prioritizes emotional aspects and passions in increasing human existence. The results of this paper to provide solutions in raising awareness of human existence, especially regarding the meaning, principles and nature of humanists in the modern era. The more aware humans are of humanist meaning and nature, the higher human existence will be. The implication, humans can reach the level of perfection in themselves without any restrictions. From these various explanations, the author hypothesizes that the concept of spiritual humanist Mulla Sadra can increase human existence and provide solutions to the crisis of human existence in the modern era.